The Emergence of the Legality Tradition in Russia, 1800-1918 - Borisova, Tatiana (My University, 2016)
This dissertation develops a historical perspective on the emergence and development of a Russian official conceptualization of legality as a condition and basis of law's performance in the late imperial period. The author argues that this tradition was articulated as 'fostering legality', and implied the formalization of law via a set of techniques designed to promote access to law and its more coherent and efficient implementation. Thus, this dissertation studies how the perception of law and legality in Russia developed in the eyes of those who created the law and made it function. It examines how law was facilitated via legal techniques by those who promoted the professionalization of law and legality in Russia. These techniques were: (a) the systematization of newly published law in the Digest of laws of the Russian empire and its continuation (Svod zakonov Rossisskoi imperii); and (b) obligatory publication of legislation. These legal techniques are considered as practices for making and reproducing a Russian legal tradition forming the basis of a specific identity of the Russian legal community which is being reproduced. The chapters of the dissertation are to answer the following questions (in chronological order): 1. how legislation was published, systematized and codified and distributed around the country; 2. why particular legal procedures for publication, systematization and codification were chosen; 3. and finally and most importantly, what these procedures tell us about Russian legality in terms of its basic aims and values. The last chapter is devoted to the revolutionary changes in the publication of law in 1917-18, since the revolutionary period is essential in the sense that it enables us to think of continuities in Russian legal tradition. The analysis of the emergence and development of the tradition of Russian legality explains the overwhelmingly technical Russian approach to law in general. The remarkable ambivalence in the Russian reception ideas of the authority of law from the West may be portrayed in the very discussion on two different types of legality: 'universal legality' and 'legality with characteristics'. In the nineteenth century the latter was articulated as 'autocratic legality'. It is important to note that 'universal legality' was a concept used by Russian legal professionals in order to stress that there are some generally accepted legal principles and concepts that could not be overruled, since they make the basis of law as an institution and do not derive from the will of the state. In contrast to 'universal legality', 'autocratic legality' seen by political leadership as technical was articulated as a benchmark of the Russian legality tradition. Its tasks were to modernize Russia and protect Russian national traditions. These rather contradictory tasks resulted in the two main characteristics of the official Russian understanding of legality: (a) its focusing on legal certainty and the prevention of arbitrariness without focusing on procedural rights; and (b) allowing administrative interventions in case of political necessity.

Venäjän virallisen laillisuuskäsitteen synty ja kehitys, 1800-1918 Tässä väitöskirjassa tarkastelen historiallisesta näkökulmasta Venäjän virallisen laillisuuskäsityksen syntyä ja kehitystä lain toimivuuden edellytyksenä ja sen pohjana myöhäisellä imperialistisella ajalla. Väitän, että tämä traditio näyttäytyi ‘laillisuuden vaalimisena’, mikä tarkoitti lakien muodollisuuden korostamista tekniikoilla, jotka oli suunniteltu edistämään oikeuden saatavuutta ja sen yhdenmukaisempaa ja tehokkaampaa täytäntöönpanoa. Väitöstyössäni tutkin näin ollen, kuinka käsitys laista ja laillisuudesta kehittyi Venäjällä niiden silmissä, jotka säätivät lain ja panivat sen täytäntöön. Tarkastelen sitä, kuinka lain merkitystä vahvistettiin oikeudellisilla tekniikoilla niiden toimesta, jotka kannattivat oikeuden ammattimaistumista Venäjällä. Nämä tekniikat olivat (a) vasta julkaistujen lakien systematisointi lakikodifikaatioihin (Svod zakonov Rossisskoi imperii) (b) lakien pakollinen julkaiseminen. Pidän näitä tekniikkoja venäläistä oikeutta luovina ja uudelleen tuottavina käytäntöinä, jotka ovat muovanneet pohjan erityiselle venäläiselle oikeusyhteisön identiteetille, jota tuotetaan näissä käytännöissä yhä uudelleen. Väitöstutkimukseni luvut vastaavat seuraaviin kysymyksiin (kronologisessa järjestyksessä): 1. Kuinka lainsäädäntö julkaistiin, systematisoitiin ja kodifioitiin sekä levitettiin ympäri maata; 2. Miksi juuri tietyt oikeudelliset käytännöt julkaisulle, systematisoinnille ja kodifioinnille tulivat valituiksi; 3. Ja viimeisenä ja tärkeimpänä kysymyksenä, mitä nämä valitut käytännöt kertovat laillisuuskäsitteestä Venäjällä, sen perustavista tavoitteista ja arvoista. Viimeinen luku on omistettu lakien julkaisussa tapahtuneille vallankumouksellisille muutoksille vuosina 1917-18, sillä vallankumousaika on keskeinen siinä mielessä, että se mahdollistaa jatkumoiden tarkastelun venäläisessä oikeudellisessa perinteessä. Venäläisen laillisuuskäsityksen synnyn ja kehityksen analysointi selittää erittäin teknisesti painottuneen venäläisen lähestymistavan lakiin ylipäätään. Huomattava ambivalenssi siinä, miten Venäjällä on omaksuttu lännestä lain auktoriteettia koskevia ideoita , voidaan kuvata kahden laillisuustyypin välisenä keskusteluna: ‘universaalin laillisuuden’ ja ‘erityispiirteisen laillisuuden’. 1800-luvulla jälkimmäisestä käytettiin termiä ‘autokraattinen laillisuus’. On tärkeää huomata, että venäläiset oikeusoppineet käyttivät ‘universaalia lailisuutta’ konseptina, jonka tarkoitus oli painottaa, että on olemassa joitakin yleisesti hyväksyttyjä oikeudellisia periaatteita ja käsitteitä, joita ei voida ohittaa, koska ne muodostavat oikeuden institutionaalisen perustan eivätkä ole johdettavissa valtiovallan tahdosta. ‘Universaalin laillisuuden’ vastakohtana ‘autokraattinen laillisuus’, jota poliittinen johto piti teknisluonteisena, asetettiin mittapuuksi venäläiselle laillisuusperinteelle. Sen tehtävänä oli Venäjän modernisointi ja venäläisten kansallisten perinteinen suojeleminen. Nämä varsin vastakohtaiset tavoitteet johtivat kahteen venäläisen virallisen laillisuuskäsityksen pääpiirteeseen: (a) sen keskittymiseen oikeusvarmuuteen ja mielivallan estämiseen kuitenkaan keskittymättä prosessuaalisiin oikeuksiin; ja (b) hallinnollisten interventioiden mahdollistamiseen poliittisen tilanteen niin vaatiessa.